2005
DOI: 10.1145/1101530.1101559
|View full text |Cite
|
Sign up to set email alerts
|

Author's comments on Gröhn, Lokki, and Takala, ICAD 2003

Abstract: Historical background and motivation for ICAD2003 paper is presented. In addition, the research results followed up is briefly overviewed and future work is elaborated. HISTORICAL CONTEXTIdeally virtual reality (VR) is multimodal, meaning that applications should provide feedback to all senses, including visual, aural, and haptic feedback, in order to immerse a user into a virtual world. However, audio is seldom applied and 3D auditory displays are rarely constructed in cavelike systems [Cruz-Neira et al. 1992… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[Participant G] Lokki and Gröhn [21] [22] [29] show that audio cues are less accurate for locating sound sources than visual cues, which is supported by comments made by our expert users during interview. However, they conclude that the encoding of elevation information into the auditory cue assists subjects ability to locate their source.…”
Section: Auditory Navigationmentioning
confidence: 75%
“…[Participant G] Lokki and Gröhn [21] [22] [29] show that audio cues are less accurate for locating sound sources than visual cues, which is supported by comments made by our expert users during interview. However, they conclude that the encoding of elevation information into the auditory cue assists subjects ability to locate their source.…”
Section: Auditory Navigationmentioning
confidence: 75%
“…Indeed, an audiovisual navigation aid is surely more performant than a navigation that consists solely of either acoustic or visual pointers [3,4,7]. The direct comparison between solely acoustic or visual pointers showed that both are equally effective.…”
Section: Navigation With Auditory Cuesmentioning
confidence: 99%